ANALISIS PERILAKU NASABAH DALAM MEMILIH PRODUK BERTEMAKAN ARSENAL DI BANK MUAMALAT SURABAYATAHUN 2017 - Dea Switani Juniar; Sugeng Hariadi; Irzameingindra Putri Radjamin (Perpustakaan Universitas Surabaya, 2018)
Football club has now become a main interest for most people in the whole world. Football club is considered to be profitable as working partners because of their massive fans all around the world. These days, many companies uses football club as a brand of their products, including financial sector in Indonesia. Some banks in Indonesia also uses football club as their partners to gather customers to buy their products. This study uses primary data collectionwhich was obtained through direct interviewsof theBank Muamalat’s customer in Surabaya as a case study.This study use qualitative approach and triangulation datamethod. The results of the interviewsof the six respondents indicates that there is a huge influence on the behavior bank’s customers in choosing Arsenal brand products. This study was intended to raise the customers’ interests of Islamic banks’ products, so the Islamic banks cancompete with the conventional banks in the future.